Pengaruh Gaya Kepemimpinan, Disiplin Kerja dan Pelatihan terhadap Kinerja Karyawan di RS. Martha Friska Brayan Medan - Basmaida Waty Tambusay; Syaiful Bahri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The aim of this study was to determine the effect of leadership style, work discipline and training on the performance of employees at Martha Friska Brayan Hospital in Medan. The research method used is quantitative analysis where the variables are measured using a Likert scale. The data collection method is done using a questionnaire. The study was conducted using a validity sample of 61 people taken from the total population of 61 people. Data processing using SPSS version 24 software with descriptive analysis, classical hypothesis testing, multiple linear regression analysis, hypothesis testing and coefficient of determination (R2). The results showed that (1) the leadership style obtained a t-count value of 2,928, which was higher than the table of 1,672. Thus, the leadership style variable had a positive and significant effect in part. on the performance of hospital employees (2) Work discipline obtained an account value t of 3,929 is greater than the table t. Thus, the work discipline variable partly has a positive and significant effect on the performance of hospital employees. (3). For the training variable, the results of t-count 4,302 are higher than those of table t, which means that partially the training variable has a positive and significant effect on the performance of hospital employees. Martha Friska Brayan Medan. (4) Simultaneously, a value of 19.746 is obtained, which is greater than the f table of 2.77. Thus, simultaneously, the independent variables, leadership style, work discipline and training have a positive and significant effect on the performance of employees of Martha Friska Brayan Medan Hospital.